PELAKSANAAN PENGAWASAN DALAM MENINGKATKAN DISIPLIN PERSONEL TENTARA NASIONAL INDONESIA DI DEPO PENDIDIKAN KEJURUAN RESIMEN INDUK DAERAH MILITER XII/TPR KOTA SINGKAWANG - M. Pangaribuan E.21111108 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This article departs from the phenomenon of lack of discipline fraction DODIKJUR personnel, as no entry charge, late, leave work early, do not obey the rules of dress and head out of the office without permission, and this is because the control has not been effective so that the necessary oversight attached. The goal is to improve the discipline of the army personnel in Depo Vocational Education Parent Regiment Military Region XII / TPR Singkawang. To find attached surveillance has been done by using three indicators, namely the leadership of monitoring, inspection and appraisal or evaluation can thus be known until the stages which form of supervision conducted by leaders in Depo Vocational Education Parent Regiment Military Region XII / TPR Singkawang. Monitoring of all activities carried out by subordinates rated as good, although there is still a relatively small deviations. Examination of all the activities carried out by subordinates rated as good, although there is still a lack of assessment conducted fairly and as small personnel. Assessment of all the activities done by the staff was good. Suggested further enhanced surveillance monitoring inherent aspect because there are indications of violation of discipline even though it was relatively small in percentage terms. Should maintain and even increase further in carrying out the policy and inspection program for monitoring activities in order to improve discipline subordinates adhere better future. Assessment should be carried out under the supervision of a tiered inherent in Dodikjur's leaders to be more objective so that subordinates do not feel any difference made ??in the implementation and enforcement.Keywords: Embedded Control, monitoring indicators, personnel discipline.